A biomechanical comparison of dominant versus non-dominant leg during single leg landing among female volleyball recreational players - Mansor, Nadhirah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Volleyball has become one of the most participated sports in the world. Participation requires knowledge of many physical skills, and performance and usually depends on the individual's ability to jump and land. An ACL injury is a tear or sprain of the anterior cruciate ligaments (ACL). Most sports-related non-contact ACL injuries occur during landing and may be caused by lower limb biomechanical abnormalities or imbalances in the dominant and non-dominant limbs. Abnormal loading of a particular limb may cause unnatural forces to be absorbed at the joints of the loaded and/or unloaded limb. The purpose of this study is to compare the biomechanical of dominant and non-dominant leg during single leg landing among female volleyball recreational players. Fifteen female university recreational volleyball players (22years old) were recruited in this study. Fourteen from the participants were having the right leg as their dominant leg. They performed three times three-dimensional (3D) Single Leg Landing (SLL) test on both dominant and non-dominant legs. The lower extremity joint which is the ankle, hip and knee kinematics and kinetics was evaluated using the Qualisys Motion Capture System. All the three joints were compared among the two phases which are the initial contact and maximum vertical ground reaction force (mVGRF) using paired t-test. The paired t-test was used to know if there were any significant differences between the dominant and non-dominant legs during SLL. As a result, there were high variability of significant result for comparison between the dominant and non-dominant legs on frontal plane kinematics (angle) and kinetics (moments) of lower extremity joints (ankle, hip and knee). According to right-hand rule, a larger hip adduction is found when women land with non-dominant legs in the maximum vGRF phase for both kinematic and kinetic. In kinematics, non-dominant leg showed greater knee adduction (1.48o, p = 0.27) during initial contact meanwhile during maximum vGRF non- dominant leg showed greater ankle adduction (1.01o, p = 0.24). Meanwhile in kinetics, non-dominant leg showed greater ankle moment (0.30 Nm/kg, p < 0.05) and hip moment (0.28 Nm/kg, p = 0.15) compared than dominant leg during initial contact. Meanwhile, during maximum vGRF, non-dominant leg showed greater hip moment (3.06 Nm/kg, p < 0.05) and knee moment (1.84 Nm/kg, p < 0.05). However, greater knee valgus during landing was found in the non-dominant limb and may indicate that landing with non-dominant leg may increase the risk of non-contact injury among female recreational volleyball players. Therefore, coaches and players are suggested to include more specific training focusing on the developing hip and thigh muscle strength on non-dominant leg. Also, they should focus on both legs strengthening during training and competitions to make them land safely, because they are vulnerable to non-contact injuries.